Old Testament theology : Israel's life /. - Goldingay, John. (Downers Grove, Ill. : InterVarsity Press, 2009)
In this third volume of his critically acclaimed Old Testament Theology John Goldingay explores the Old Testament vision of Israel's life before God. The first volume focused on the story of God's dealings with Israel, or Israel's gospel. The second volume investigated the beliefs of Israel, or Israel's faith. Now the spotlight falls on the Old Testament's perspective on the life that Israel should live in its present and future, including its worship, prayer and spirituality, as well as its practices, attitudes and ethics before God. --from publisher description.
Introduction: Gospel, faith, life -- Part One: Living with God. Submission and celebration ; Prayer and thenksgiving -- Part Two: Living with one another. Family and community ; City and nation -- Part Three: Living with ourselves. Spirituality and character ; Leaders and servants -- Conclusion.
Includes bibliography (p. [840]-872) and indexes.
Keywords: Bible. -- Criticism, Narrative; Narration in the Bible